1993
DOI: 10.1128/jb.175.7.2017-2025.1993
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of pathogenicity of avirulent Xanthomonas oryzae pv. oryzae and X. campestris pathovars by reciprocal complementation with the hrpXo and hrpXc genes and identification of HrpX function by sequence analyses

Abstract: The molecular basis of pathogenesis by Xanthomonas oryzae pv. oryzae has been partly elucidated by the identification of a gene, hrpXo, required for bacterial blight on rice. A mutation in hrpXo results in the loss of pathogenicity on rice and the loss of hypersensitivity on nonhosts such as Datura stramonium and radishes. Pathogenicity and its ability to cause Xanthomonas oryzae pv. oryzae (30), a yellow-pigmented gram-negative member of the family Pseudomonadaceae, causes bacterial blight on rice, a diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
2

Year Published

1996
1996
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 40 publications
(37 reference statements)
1
37
0
2
Order By: Relevance
“…The hrpXv gene is located at the extremity of the insert of pXV751 on a 2.5-kb EcoRI-HindIII (vector site) fragment that was subcloned in pBluescript-KS II (pBX10) and partially sequenced. Comparison of the obtained sequence with the published sequences of hrpXo (31) and hrpXc (40) indicated that the hrpXv gene was only partially present in the cosmid clones. We therefore cloned the genomic 9.4-kb EcoRI fragment described above from X. campestris pv.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The hrpXv gene is located at the extremity of the insert of pXV751 on a 2.5-kb EcoRI-HindIII (vector site) fragment that was subcloned in pBluescript-KS II (pBX10) and partially sequenced. Comparison of the obtained sequence with the published sequences of hrpXo (31) and hrpXc (40) indicated that the hrpXv gene was only partially present in the cosmid clones. We therefore cloned the genomic 9.4-kb EcoRI fragment described above from X. campestris pv.…”
Section: Resultsmentioning
confidence: 93%
“…Sequences homologous to the hrpX gene of X. campestris pv. campestris are present in several Xanthomonas species (31). To find out whether X. campestris pv.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…armoraciae. This result indicates that hrpXo and hrpXc are functionally equivalent [30]. PCR amplification of hrpXo in 16 X. campestris pathovars and 12 X. oryzae pv.…”
Section: Hypersensitive Response and Pathogenicity (Hrp) Genesmentioning
confidence: 99%
“…PCR amplification of hrpXo in 16 X. campestris pathovars and 12 X. oryzae pv. oryzae strains indicates that the hrpX gene is highly conserved in Xanthomonas and suggests that the functional equivalence may extend into other pathovars of X. campestris [30,31]. By using a portion of the X. campestris pv.…”
Section: Hypersensitive Response and Pathogenicity (Hrp) Genesmentioning
confidence: 99%